2005
DOI: 10.1113/jphysiol.2005.083840
|View full text |Cite
|
Sign up to set email alerts
|

Prior heavy exercise eliminates slow component and reduces efficiency during submaximal exercise in humans

Abstract: We investigated the hypothesis that the pulmonary oxygen uptake (V O 2 ) slow component is related to a progressive increase in muscle lactate concentration and that prior heavy exercise (PHE) with pronounced acidosis altersV O 2 kinetics and reduces work efficiency. Subjects (n = 9) cycled at 75% of the peakV O 2 (V O 2 peak ) for 10 min before (CON) and after (AC) PHE.V O 2 was measured continuously (breath-by-breath) and muscle biopsies were obtained prior to and after 3 and 10 min of exercise. Muscle lacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
75
2
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(95 citation statements)
references
References 38 publications
13
75
2
5
Order By: Relevance
“…The retained hyperbolic P-t lim characteristic is consistent with its underlying determinants collectively continuing to change either linearly or exponentially with time toward some limiting value, at a rate proportional to work rate and therefore the rate of WЈ utilization (40), but with a reduction in the limiting value and/or an increase the rate at which it is approached. With regard to the latter scenario, for example, the demonstration of an increased fundamental V O 2 asymptote suggests a reduction in work efficiency (whose origin remains uncertain; see above), which would be expected to require a greater degree of PCr breakdown and therefore exacerbate depletion of a previously incompletely replenished intramuscular PCr store (48). On the other hand, the degree of exercise-induced metabolic-acidemic stress in both blood (17,18) and muscle (42,48) has been shown to be reduced.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The retained hyperbolic P-t lim characteristic is consistent with its underlying determinants collectively continuing to change either linearly or exponentially with time toward some limiting value, at a rate proportional to work rate and therefore the rate of WЈ utilization (40), but with a reduction in the limiting value and/or an increase the rate at which it is approached. With regard to the latter scenario, for example, the demonstration of an increased fundamental V O 2 asymptote suggests a reduction in work efficiency (whose origin remains uncertain; see above), which would be expected to require a greater degree of PCr breakdown and therefore exacerbate depletion of a previously incompletely replenished intramuscular PCr store (48). On the other hand, the degree of exercise-induced metabolic-acidemic stress in both blood (17,18) and muscle (42,48) has been shown to be reduced.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the latter scenario, for example, the demonstration of an increased fundamental V O 2 asymptote suggests a reduction in work efficiency (whose origin remains uncertain; see above), which would be expected to require a greater degree of PCr breakdown and therefore exacerbate depletion of a previously incompletely replenished intramuscular PCr store (48). On the other hand, the degree of exercise-induced metabolic-acidemic stress in both blood (17,18) and muscle (42,48) has been shown to be reduced. An alternative scenario that is consistent with the P-t lim relationship remaining well described by a hyperbola is that, for any supra-CP work rate, V O 2max is reached prior to complete WЈ depletion, but when a constant percentage of the fully depleted WЈ is reached; i.e., the remaining portion being functionally inaccessible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the k would suggest that the increase in O 2 was also faster during the C-R condition, indicating that steady-state could have been reached earlier following prior moderate intensity cycling exercise. The cause of the changes observed during the first minute of the C-R condition are not fully 275 understood, but may have resulted from an enhanced muscle oxygen supply (DeLorey, Kowalchuk, Heenan, Dumanoir, & Paterson, 2007), an increase in blood flow (Krustrup, Gonzalez-Alonso, Quistorff, & Bangsbo, 2001) and/or improved oxidative enzyme activity (Sahlin, Sorensen, Gladden, Rossiter, & Pedersen, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Sahlin et al (2005) have shown that GE is reduced when cycling at a moderate intensity following three high intensity (110% ̇2 max ) efforts. This suggests that efficiency is attenuated following supramaximal exercise.…”
Section: Power Metersmentioning
confidence: 99%